Students’ Perceptions of a Web-Based TOEIC Prediction ‎Platform for Autonomous English Learning - Yusri; Peter Crosthwaite; Sulistya Ningrum; Ahmad Iman Mulyadi; Annisa Karya; M. Julio Alkindy; Putri Shara (JPI: Jurnal Pustaka Indonesia, 2026)
This study explores the use of TOEIC Prediction Website as a digital learning platform in supporting students’ English proficiency development and TOEIC preparation. The objective of the study is to explore the role of the platform as a learning support system and its motivating role in the students’ involvement in a web-based learning environment. A descriptive quantitative was applied by using a questionnaire which was distributed to 72 students of the D-III English Study Program of Politeknik Negeri Sriwijaya. Descriptive analysis was performed on the data to explore students’ perceptions of the usefulness of the platform, the learning support features and the role it played in encouraging engagement. The results suggest that the TOEIC Prediction Website is successful in facilitating learning by providing structured practice resources, immediate feedback, and flexible accessibility, thereby helping students to understand TOEIC test formats and enhancing their learning experience. The platform also fosters behavioral, cognitive, and emotional engagement through active participation, independent learning, and continuous motivation. These results suggest that incorporating instructional support and engagement elements in digital learning settings may help prepare students for standardized English proficiency tests. The research indicates that the TOEIC Prediction Website has a promising potential as an alternative learning tool for TOEIC preparation in higher education contexts